First Results from new High-precision Measurements of Deflections of the Vertical in Switzerland - Muller, A.; Burki, B.; Kahle, H.; Hirt, Christian; Marti, U. (Springer, 2004)
In October 2003 two modernized digital zenith camera systems have been deployed in Switzerland during the campaign CHGeo2003. The mission was carried out under the auspices of the Swiss Geodetic Commission of the Swiss Academy of Sciences (SAS) and coordinated by the Swiss Federal Office of Topography (swisstopo). The goal of the campaign was to provide additional highly accurate deflections of the vertical in order to contribute to an improvement of the presently used Swiss geoid CHGeo98. The observations were carried out at 68 selected stations covering regions with old or inadequate data. Further reasons of the campaign were the proof of the field capability and the comparison of both systems concerning their accuracy by observing at several stations simultaneously. The paper describes the realization of the campaign CHGeo2003 and the results obtained with the digital systems.